2019
DOI: 10.26832/24566632.2019.040302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and inorganic fertilizer combination with insect netting on the production of Indian spinach (Basella alba L.)

Abstract: Best horticulture management has been practiced to reduce the quantity of inorganic fertilizer applications with insect net for higher production of Indian spinach (Basella alba L.). The experiment was conducted at the Horticulture Farm of Bangladesh Agricultural University (BAU), Mymensingh during February to May, 2016. Two factors experiment were conducted on insect nettings (Factor A): control (N 0), Netting (N 1) and different fertilizers (Factor B): control (F 0), Vermicompost 10 t/ha (F 1), Vermicompost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…With increasing amounts of MOF up to 25 tons per ha, fresh mass, theoretical yield and actual yield were increased in lettuce and mustard spinach. In a previous report, Akther et al (2019) found that the yield of Indian spinach increased with increasing amounts of vermicompost, and it was higher than 35 tons per ha in the combination of fertilizer and insect netting. Also, increasing levels of organic fertilizer prepared from meat and bone The means with similar lower-case letters within columns did not differ significantly at 5% probability; F1: Moringa organic fertilizer (MOF); F2: Cow manure; F3: Bioorganic fertilizer; Control: without fertilization; LSD: Least significant difference.…”
Section: Discussionmentioning
confidence: 88%
“…With increasing amounts of MOF up to 25 tons per ha, fresh mass, theoretical yield and actual yield were increased in lettuce and mustard spinach. In a previous report, Akther et al (2019) found that the yield of Indian spinach increased with increasing amounts of vermicompost, and it was higher than 35 tons per ha in the combination of fertilizer and insect netting. Also, increasing levels of organic fertilizer prepared from meat and bone The means with similar lower-case letters within columns did not differ significantly at 5% probability; F1: Moringa organic fertilizer (MOF); F2: Cow manure; F3: Bioorganic fertilizer; Control: without fertilization; LSD: Least significant difference.…”
Section: Discussionmentioning
confidence: 88%
“…In short, the combination of organic and inorganic fertilizers can reduce the use of inorganic fertilizers (Sunarpi et al, 2021). The simultaneous application of organic and inorganic fertilizers is also to improve soil and environmental health in the long term (Akther et al, 2019).…”
Section: Farmers Do Not Yet Know the Content Of Rice Straw And Its Be...mentioning
confidence: 99%
“…Kombinasi pupuk organik (50%) dan anorganik pupuk (50%) dapat meningkatkan pertumbuhan dan hasil padi dibandingkan dengan diberi pupuk anorganik 100%. Singkatnya, kombinasi organik dan pupuk anorganik dapat mengurangi penggunaan pupuk anorganik [27] Aplikasi pupuk organik dan anorganik secara bersamaan juga untuk meningkatkan kesehatan tanah dan lingkungan dalam jangka Panjang [28].…”
Section: Petani Masih Pesimis Akan Manfaat Bahan Organik Dalam Memper...unclassified